parallel lines have the same slopes so to find the slope of our equation, we first find the slope of the given equation
to find the slope of -3x - 6y = 17
we convert it to slope intercept form, y = mx + b
where m would be our slope
6y = -3x - 17
y = (-1/2)x - (17/6)
m = (-1/2)
so our slope is (-1/2)
then we would create the equation with the slope -1/2 and the given point (6, 3)
so we have
y = -1/2 x + b
we temporarily plug in the point (6,3) for (x,y)
3 = (-1/2)(6) + b
3 = -3 + b
b = 6
so we get the equation
y = (-1/2)x + 6